A Theological Model of Healing to Inform an Authentic Healing Ministry - Bate, Stuart (Journal of theology for Southern Africa, 2012)
Healing was an important part of the mission of Jesus and the apostles. This ministry continued throughout the history of the Church, taking many forms. Plagues, pandemics and incurable diseases have always been a challenge to it. This challenge has been of a contextual theological model which can inform the healing ministry within Southern Africa. The narrative is constructed in terms of seven challenges which must be met to ensure this goal is reached. Three of the challenges respond to issues emerging from a miraculous cures and those who believe primarily in medical procedures. The other four challenges respond to issues emerging from a theological analysis of the context. An assessment is made of the theological merits of diverse healing procedures.
Free
Keywords: AIDS (Disease); City churches; Diseases – Religious aspects; Diseases – Social aspects; HIV (Viruses); Healing in the Bible; Healing; Spiritual; Peer reviewed; Theology – South Africa; Theology; Contextual